Branding Produk Sebagai Solusi UMKM di Masa Pandemi - Abdurrahman, Ginanjar; Wahanggara, Victor (Indonesian Journal Publisher, 2021)
One of the major threats in today's economic world is Corona Virus Disease 2019 (Covid-19). With this virus, of course, has a big impact and becomes an obstacle to various sectors of the Indonesian economy, especially MSMEs. Product branding is a solution for MSMEs to have economic resilience during the Covid-19 Pandemic. Based on the problems faced by partners, the solution proposed in the PKM Stimulus this time is to provide additional insight to partners (MSMEs) about product branding, so that it is hoped that MSMEs are easy to market products, right in ordering, easy to recognize, and loyal customers. The solutions provided are activities that provide knowledge and insight for MSMEs in knowing and understanding product branding as a solution for MSMEs, especially during the Covid-19 pandemic, so that MSMEs can survive the Covid-19 Pandemic. Participants participated in this activity enthusiastically. The event began with registration, followed by reading the curriculum vitae. Then the speaker gave a presentation on Product Branding for 30 minutes, followed by a discussion with the participants. After 2 question sessions, there were still those who wanted to ask questions, so there was another question session opening by giving the opportunity to 2 questioners. So that it can be indicated that the socialization participants welcomed the training activities positively.